PEMBERDAYAAN KADER KESEHATAN DAN MASYARAKAT DALAM PENANGANAN DAN PENCEGAHAN STUNTING PADA 1.000 HARI PERTAMA KEHIDUPAN - Eka Sutrisna; Maulida, Husna; Suriani, Suriani (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The problems in Gampong Jambo Mesjid are the high rate of Stunting, namely 23 people, lack of public knowledge about nutritious food at the first 1000 days, feeding methods and eating patterns, low support and awareness of husbands and families in improving the nutritional status of toddlers, low community income, factors food taboos where certain nutritious foods cannot be consumed by children under five, low coverage of exclusive breastfeeding, lack of awareness in handling stunting in toddlers, and lack of awareness of preventing stunting in toddlers. This community service activity aimed to increase the knowledge of cadres and the community in handling and preventing stunting in the first 1000 days of life. The method of implementing this activity is in the form of training and counseling on providing nutritious food to the first-1000-days, feeding methods and eating patterns, practice of providing additional food that is age appropriate. The results achieved from this activity are increasing the knowledge and skills of cadres and the community in handling stunting, increasing body endurance, optimal growth and development, increasing quality human resources towards a stunting-free Lhokseumawe City.